Increase Financial Capital of Top Glove in Order to Improve Environment and Sustainability: The Case of Top Glove - Michelle Zi Ying Wu; Daisy Mui Hung Kee; Yuan Kun Loo; Shie Jie Goh; Hani Jumah Alyanbaawi (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
Nowadays, global warming has become serious environmental issue that may affect humans and other living organisms. This is caused by the emissions of greenhouse gases. This problem has also led to climate change which will bring impacts to business, community and the environment. Therefore, it is everyone’s responsibility to face this environment issues. Top Glove contributes the emission of carbon dioxide as the employees operate the machines using fossil fuels. In 2018, their gas consumption was at 16.98kg carbon dioxide emissions per carton of gloves produced. In line with recognizing the effect of climate change, they aim to reduce 8% of carbon dioxide emission annually. Thus, they have applied biomass which is renewable energy at 6 factories to tackle this problem. However, we need to encourage more renewable energy by expanding the application of this green energy throughout Top Glove factories. Top Glove face the problem of insufficient financial capital to invest the modern technology for every factory. Hence, they need to solve the problem of their financial problem in order to improve environment issues. Next, Top Glove is the world’s largest manufacturer of gloves and it was founded since 1991. It has proficient experiences in manufacturing gloves. One of many reasons behind this success is they have an effective and efficient system in managing company. Besides that, they also take care of the well-being of their employees. Furthermore, they introduce environment friendly product to the community. As this paper will show, there is still changes and improvement that can be made, in order to integrate sustainability well into Top Glove’s business strategy.